Tannin-tolerant bacteria from crossbred Holstein x Zebu cows - Arcuri, Pedro Braga; Odenyo, Agnes Awino; Arcuri, Edna Froeder; Ribeiro, Marlice Teixeira; Guimarães, Marta Fonseca Martins; Carneiro, Jailton da Costa (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to isolate and characterize tannin-tolerant ruminal bacteria from crossbred Holstein x Zebu cows fed a chopped mixture of elephant grass (Pennisetum purpureum), young stems of "angico-vermelho" (Parapiptadenia rigida), and banana tree (Musa sp.) leaves. A total of 117 bacteria strains were isolated from enrichment cultures of rumen microflora in medium containing tannin extracts. Of these, 11 isolates were able to tolerate up to 3 g L-1 of tannins. Classical characterization procedures indicated that different morphological and physiological groups were represented. Restriction fragments profiles using Alu1 and Taq1 of 1,450 bp PCR products from the 16S rRNA gene grouped the 11 isolates into types I to VI. Sequencing of 16S rRNA PCR products was used for identification. From the 11 strains studied, seven were not identifiable by the methods used in this work, two were strains of Butyrivibrio fibrisolvens, and two of Streptococcus bovis.